Analisis Konsumsi Energi Rumah Tangga Perkotaan di Indonesia: Periode Tahun 2008 dan 2011 - Nazer, Muhammad; Handra, Hefrizal (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
The goal of the study is to analyze the pattern and the change of urban household energy consumption and their determinant factors in Indonesia period of 2008 and 2011 using SUSENAS data of household budget survey. The concept of energy ladder and fuel stacking (multi fuel) are used to make a model of household energy consumption. The result of study shows that total energy consumption was increase in the period of 2008 and 2011. Coefficient of income elasticity toward both of modern and traditional energy consumption are positive, it means that there is rising consumption of energy along with the rising income. Household income is the main determinant factor of energy used by household besides other non-economic factors.